Les séries télévisées au prisme de l’intertextualité : quelques perspectives sur les frontières du littéraire - Ronan Ludot-Vlasak (TV Series, 2017)
Drawing on Giorgio Agamben’s definition of the concept of profanation, this article aims at offering theoretical perspectives on intertextuality in American TV series. Not only may intertextual references in TV series desecrate canonical works and challenge long-lasting interpretive traditions, but their analysis may also broaden the scope of intertextual studies and renew our approach to the literary canon. The shows explored include Battlestar Galactica (2004-2009), Queer As Folk (2000-2005) and Cold Case (2003-2010).